Associated effects of storage and mechanical pre-treatments of microalgae biomass on biomethane yields in anaerobic digestion. (October 2016) - Gruber-Brunhumer, M.R.; Jerney, J.; Zohar, E.; Nussbaumer, M.; Hieger, C.; Bromberger, P.; Bochmann, G.; Jirsa, F.; Schagerl, M.; Obbard, J.P.; Fuchs, W.; Drosg, B.
Abstract: The pre-treatment of microalgae cell walls is known to be a key factor to enhance methane (CH4 ) yields during anaerobic digestion. This study investigated the combined effects of two different biomass storage methods and physical pre-treatments on the anaerobic digestion for three different microalgae species. Acutodesmus obliquus, Chlorella vulgaris and Chlorella emersonii were cultivated in 80 L sleevebag photobioreactors (batch mode), and then subjected to different storage (cooling and freezing) and pre-treatment methods prior to anaerobic digestion using the biochemical methane potential (BMP) test. A. obliquus was selected to evaluate pre-treatment methods for further experimentation. Significantly higher CH4 yields of cooled (4 °C) A. obliquus biomass were achieved through ultrasonication (+53% CH4 ) and wet-milling (+51% CH4 ). These methods were then applied in follow-up experiments to cooled (4 °C) biomass of C. emersonii and A. obliquus . Ultrasonication again led to significantly higher CH4 yields for A. obliquus biomass (323 dm 3 kg −1 CH4 yield calculated at standard gas conditions of 273 K, and 101.5 kPa per unit volatile solids, +41% CH4 ), and C. emersonii biomass (308 dm 3 kg −1 ; +35% CH4 ). In a third experiment series, frozen A. obliquus and C. vulgaris biomass were thawed prior to pre-treatment and BMP-testing. Among all BMP tests, the highest CH4 yields were achieved with untreated, freeze-thawed C. vulgaris biomass (406 dm 3 kg −1 ); pre-treatment did not enhance CH4 yields for C. vulgaris, but for A. obliquus (ultrasonication +20%). Pre-treatment was more effective for cooled than freeze-thawed microalgal biomass and combined effects acted strain dependently. Highlights: In-house microalgae production allowed us to assess combined storage-pre-treatment-effects on methane yields. Pre-treatment effectiveness on methane yield was strongly dependent on storage conditions. Freeze-thawing of microalgae increased CH4 yields from 47% to 137%, compared to cooled microalgae depending on strain. Ultrasonication in a flow-through cell consistently increased CH4 yields of cooled (4 °C) microalgae from 35% to 53%.